Akibat Hukum Financial Technology Peer to Peer Lending Ilegal Terhadap Kewajiban dalam Perjanjian Pembayaran Utang - P.G, Ida Ayu Indira Wahyu Prameswari; Marwanto, Marwanto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Abstract : This study aims to identify and analyze the legal arrangements related to peer-to-peer (p2p) lending financial technology based on the regulations of the financial services authority in Indonesia and the legal consequences of debt repayment agreements if it is known that the fintech peer-to-peer (p2p) lending provider is illegal. The research method used in this paper is a normative legal research method with a statutory and conceptual approach. The results of this paper explain that legal arrangements related to peer-to-peer (p2p) lending financial technology in Indonesia are generally contained in Bank Indonesia Regulation No. 18/40/PBI/2016 concerning Implementation of Payment Transaction Processing, Bank Indonesia Circular Letter No. 18/22/DKSP regarding the Implementation of Digital Financial Services, Bank Indonesia Regulation No. 18/17/PBI/2016 concerning Electronic Money and Financial Services Authority Regulation of the Republic of Indonesia Number 13/POJK.02/2018 concerning Digital Financial Innovation in the Financial Services Sector. 77/POJK.01/2016 Regarding Information Technology-Based Borrowing-Lending Services, as well as Legal Consequences on Debt Payment Agreements if Known by Fintech Peer to Peer (P2p) Providers Illegal Lending is a loan agreement that can be canceled so that the borrower must return the funds to the provider such as beginning. Abstrak : Studi ini bertujuan untuk mengetahui serta menganalisis pengaturan financial technology peer to peer (p2p) lending berdasarkan peraturan otoritas jasa keuangan di Indonesia serta akibat hukum perjanjian pembayaran utang apabila menyelenggarakan fintech peer to peer (p2p) lending illegal. Metode penelitian yang digunakan dalam penulisan ini adalah metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil dari penulisan ini menjelaskan bahwa Pengaturan financial technology peer to peer (p2p) lending di Indonesia secara umum termuat dalam Peraturan Bank Indonesia No. 18/40/PBI/2016 tentang Penyelenggaraan Pemrosesan Transaksi Pembayaran, Surat Edaran Bank Indonesia No. 18/22/DKSP perihal Penyelenggaraan Layanan Keuangan Digital, Peraturan Bank Indonesia No. 18/17/PBI/2016 tentang Uang Elektronik dan Peraturan Otoritas Jasa Keuangan Republik Indonesia Nomor 13/POJK.02/2018 tentang Inovasi Keuangan Digital di Sektor Jasa Keuangan selanjutnya pengaturan yang lebih spesifik mengenai layanan pinjaman online diatur dalam Peraturan Otoritas Jasa Keuangan No. 77/POJK.01/2016 Tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi, serta Akibat Hukum Perjanjian Pembayaran Utang apabila menyelenggarakan Fintech Peer To Peer (P2p) Lending Illegal adalah perjanjian peminjaman dana menjadi dapat dibatalkan sehingga peminjam harus mengembalikan dana kepada penyelenggara seperti semula.